Exploitation des invertébrés par les sociétés précolombiennes des Petites Antilles - Nathalie Serrand (Journal de la Société des Américanistes, 2007)
Exploitation of invertebrates by the Precolumbian societies of the Lesser Antilles. Invertebrates (molluscs and crustaceans) were significant resources for the Precolumbian societies present in the West Indian islands between the VIth millenium B.C. and the xvth century A.D. Integrating them through archaeozoological analysis contributes to the definition of the socio-economical and cultural systems of these societies. Data derived from twenty one sites distributed on seven islands of the Lesser Antilles allow to sketch the evolution of the exploitation patterns during the major chrono-cultural phases. Molluscs seem to have played a role in the mobility and territorial occupation patterns of the first hunter-gatherer settlers of the Archaic period. Exploitation of invertebrates by the first sedentary groups of the early Ceramic period, shows specificities which suggest an homogenous economy, little diversified locally, reflecting a relative cultural cohesion. During the rest of the Ceramic period, the exploitation patterns appear more varied. They are characterized by changes in targets which suggest a more pragmatic and intensive managment of the resources, in a context of cultural diversification. These main trends still need to be refined with a better understanding of the paleo-environmental frame and the technical systems of these societies.